Competing through e-skills: Luxembourg and its second level digital divide - Nico Binsfeld; Jason Whalley; Lee Pugalis (International Telecommunications Society (ITS), 2016)
There is growing awareness amongst policy makers, scholars and practitioners that the Information and Communication Technology (ICT) sector plays an important role in a country's economy and welfare. The ICT sector relies on highly performing technical infrastructures but also needs skilled people who are able to understand its complexities and are fully capable of making the best use of its potential. In this article we present and discuss this tension for the case of Luxembourg, one of the smallest countries in the world whose economy is open and largely service driven. Although a lot of improvements have been made in recent years regarding its ICT infrastructure, Luxembourg performs poorly in international league tables with regards to e-skills or digital competences showing a tendency to a “second level digital divide” in terms of its ICT professionals. Drawing on a prior study which mapped Luxembourg's ICT ecosystem, we conducted qualitative interviews with human resources managers that allowed us to identify the need for relevant ICT professional skills. By applying an e-competences framework, we have identified six different families of ICT jobs that are most demanded in Luxembourg as well as their underlying competences. We then present several policy initiatives that could address the challenges faced by Luxembourg. By doing so we provide a contribution in order to better understand the issues related to e-skills and digital competences in a small country. To the best of our knowledge this is the first study of this kind looking specifically into the e-skills situation in Luxembourg
Keywords: 330; e-skills; digital divide; competences frameworks; Luxembourg; ICT